The Ubr2 gene is expressed in skeletal muscle atrophying as a result of hind limb suspension, but not Merg1a expression alone - Gregory H. Hockerman; Nicole M. Dethrow; Sohaib Hameed; Maureen Doran; Christine Jaeger; Wen-Horng Wang; Amber L. Pond (PAGEPress Publications, 2014)
Skeletal muscle (SKM) atrophy is a potentially debilitating condition induced by muscle disuse, denervation, many disease states, and aging. The ubiquitin proteasome pathway (UPP) contributes greatly to the protein loss suffered in muscle atrophy. The MERG1a K+ channel is known to induce UPP activity and atrophy in SKM. It has been further demonstrated that the mouse ether-a-gogo-related gene (Merg)1a channel modulates expression of MURF1, an E3 ligase component of the UPP, while it does not affect expression of the UPP E3 ligase Mafbx/ATROGIN1. Because the UBR2 E3 ligase is known to participate in SKM atrophy, we have investigated the effect of Merg1a expression and hind limb suspension on Ubr2 expression. Here, we report that hind limb suspension results in a significant 25.6% decrease in mouse gastrocnemius muscle fiber cross sectional area (CSA) and that electro-transfer of Merg1a alone into gastrocnemius muscles yields a 15.3% decrease in CSA after 7 days. More interestingly, we discovered that hind limb suspension caused a significant 8-fold increase in Merg1a expression and a significant 4.7-fold increase in Ubr2 transcript after 4 days, while electro-transfer of Merg1a into gastrocnemius muscles resulted in a significant 6.2-fold increase in Merg1a transcript after 4 days but had no effect on Ubr2 expression. In summary, the MERG1a K+ channel, known to induce atrophy and MURF1 E3 ligase expression, does not affect UBR2 E3 ligase transcript levels. Therefore, to date, the MERG1a channel's contribution to UPP activity appears mainly to be through up-regulation of Murf1 gene expression.